Chronic cold-stress induced histopathological changes, oxidative stress, and alterations in liver functions and nutrient composition of hybrid red tilapia and the potential protection of unsaturated fatty acids - Refaey, Mohamed M.; Mehrim, Ahmed I.; El-Komy, Magda M.; Zenhom, Osama A.; Mansour, Abdallah Tageldein (Frontiers in Marine Science, 2023)
The hybrid red tilapia (♂Oreochromis niloticus × ♀O. mossambicus) is a promising tilapia fish with high growth rate, market acceptability, and the ability to live in a wide range of salinities, but it is sensitive to low water temperature. Therefore, the objective of this experiment was to improve hybrid red tilapia resistance to chronic cold stress by increasing unsaturated fatty acids and evaluating their effects on fish body weight, hepatosomatic index (HSI), body nutrient composition, liver function enzymes, histopathological alterations, and biomarkers of oxidative stress in the gills and liver. For 98 days, fish were fed four diets based on two dietary fat sources: corn oil (a traditional source) and Aquafat-O® (a commercial product rich in high polyunsaturated fatty acids), in different ratios of 3:0 (T0), 2:1 (T1), 1:2 (T2), and 0:3 (T3), respectively. Subsequently, all groups (T0+, T1, T2, and T3) were subjected to water cold stress at 13 °C for 15 days, with half of the control group serving as a negative control (T0-; at a rearing water temperature of 25-26 °C). Chronic old stress caused significant reductions in fish body weight, HSI, aspartate transaminase and alanine transaminase activities, fat and energy contents, and oxidative stress biomarkers in the liver and gills. Red tilapia subjected to low temperatures showed severely altered histopathological conditions in the liver and gills. However, by gradually increasing the Aquafat-O® ratio in the diet, the negative effects of cold stress were mitigated. Thus, it could be concluded that the beneficial use of Aquafat-O® (as a promising fat source) at a percentage of up to 69.60 g kg-1 is necessary to cope with the cold-water stress for sensitive hybrid red tilapia.